(untitled) (Constructionism Conference Proceedings, 2025)
While constructionism has proven to be a powerful educational approach – leveraging technology to enhance learning across diverse environments – its broader adoption is often limited by traditional school structures and the perceived radical nature of its principles. A key challenge for any constructionist research group is how to effectively promote these innovative practices to a wider audience and support their integration into mainstream education. To address this, our constructionist lab has developed an innovative collaboration model that connects academia with the regional educational ecosystem. Our goal is to cultivate a thriving constructionist community that extends beyond the boundaries of academic research, bringing together schools, educational organizations, and, most importantly, the educators who shape them. The model is built on partnerships with nonprofit organizations to amplify the university’s impact beyond institutional confines. This collaboration draws on the strengths of each partner: the university contributes by developing innovative content, offering formal teacher training, and conducting rigorous evaluations of both short- and long-term impacts on students and educators. Nonprofits, on the other hand, offer the flexibility and reach to implement educational initiatives in local communities, including those in underserved areas. Their deep connection to local needs enables them to co-design initiatives from the ground up, ensuring contextual relevance and lasting impact. This study contributes insights into the replicability of our collaboration model, offering a framework that other institutions can adapt to advance constructionist methodologies in varied educational settings. By fostering collaboration among educators, researchers, and nonprofit organizations, the initiative provides a scalable approach to enabling meaningful and sustainable transformations in teaching and learning practices.